Siblings in Parallel: The Significance of Jesus Calling Mary and Lazarus in John 11 - Feník, Juraj (Neotestamentica, 2024)
This article aims to show that the story of the raising of Lazarus in John 11 contains a conceptual similarity between Mary and Lazarus, namely, their calling by Jesus. In particular, the episode devoted to Jesus's meeting with Mary (11:28-37) includes Martha's clandestine admission to her sister that Jesus is calling her (v. 28), which is followed by Mary's immediate departure from the house to Jesus (v. 29), who has not yet entered the village (v. 30). Aside from other dimensions of the story, Jesus is here portrayed as the one who calls Mary out of the house to a meeting with him. A similar dynamic is found in the episode of Lazarus's exit from the grave (11:38-44); for here Jesus is the one who calls Lazarus out of the tomb (v. 43), which results in his immediate compliance (v. 44). Verse 12:17 lexicalizes Jesus's action as a "call," thus securing a lexical and conceptual resemblance to his call of Mary. By attending to these and related lexical features, this article argues that the story in John 11 contains two calls: a call of Mary and a call of Lazarus. As such, it offers a contribution to the research on the parallels between men and women in the Fourth Gospel.